Dampak Program Revitalisasi Kakao Terhadap Pengembangan Kelompok Tani Kaitannya Terhadap Pendapatan di Kecamatan Kodeoha Kabupaten Kolaka Utara - Arhan, Arhan; Irwan Halid; Taruna Shafa Arzam AR (SINTA Journal (Science, Technology, and Agricultural), 2025)
This study aims to evaluate the role of farmer groups in the cocoa revitalization program towards increasing farmer income in Era Baru Village, Kodeoha District, North Kolaka Regency. The method used is a descriptive quantitative approach with paired sample t-test analysis to see the difference in income before and after the program. The results of the study indicate that the cocoa revitalization program has a positive impact on farmer income. The average farmer income increased from Rp 22,302,811 to Rp 23,802,189, with an average difference of Rp 1,479,377.78. The t-test shows a significant value of 0.000 (p < 0.05), which means there is a statistically significant difference between income before and after the program. From the institutional aspect, the average score of farmer group development is in the growth category (56.39%), with extension services having the highest score (76.30%). Meanwhile, aspects of organization and leadership (44.81%), member participation (51.11%), and group performance and results (53.33%) still require strengthening. These results confirm that, in addition to technical improvements in cocoa cultivation, strengthening farmer group institutions is a crucial factor in the program's success. Further strategies such as managerial training, increasing young farmer participation, and strengthening market access and partnerships are needed to ensure the revitalization program's impact is sustainable and equitable across all farmer group members.Â